Two emergency cases of spontaneous esophageal perforation treated using a minimally invasive abdominal and left thoracic approach. Issue 3 (17th September 2019) - Sekiya, Sho; Ebihara, Yuma; Yamamura, Yoshiyuki; Tanaka, Kimitaka; Nakanishi, Yoshitsugu; Asano, Toshimichi; Noji, Takehiro; Kurashima, Yo; Murakami, Soichi; Nakamura, Toru; Tsuchikawa, Takahiro; Okamura, Keisuke; et al.
Abstract: Boerhaave's syndrome is a rare life‐threatening disease that requires prompt intervention. Thoracotomy has traditionally been considered the gold standard approach for treatment, but other minimally invasive approaches have recently been reported. Our institute reported the efficacy of minimally invasive abdominal and left thoracic approach in the treatment of patients with esophagogastric junction cancer and introduced it for the treatment of two patients with Boerhaave's syndrome. We intraoperatively sutured the rupture sites and irrigated the pleural cavity using thoracoscopy. Then, after confirming the absence of intraabdominal contamination, we performed jejunostomy or gastrostomy using laparoscopy. Patients' vital signs remained stable intraoperatively, and their postoperative periods were uneventful with no leakage or stricture. The minimally invasive abdominal and left thoracic approach for Boerhaave's syndrome is convenient and useful as it provides excellent visualization of the thoracic and abdominal cavities with the possibility of quickly switching between views.